1941
DOI: 10.1002/srin.194100586
|View full text |Cite
|
Sign up to set email alerts
|

Der Unterschied zwischen mechanisch und röntgenographisch ermittelten Elastizitätskonstanten

Abstract: Vergleichsversuch zur Spannungsmessung an einem Biegestab mit gleichartiger Versuchsführung in beiden Instituten. Auswertung zur Bestimmung der röntgenographischen Elastizitätskonstanten. Mechanische Dehnungsmessungen. Nachweis von Unterschieden zwischen rönlgenographischer und mechanischer Dehnungsmessung. Folgerungen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1958
1958
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…diffraction strains differ from mechanical strains due to the intrinsic elastic anisotropy. Diffraction (X-ray) elastic constants were eventually proposed on an empirical basis by Mö ller & Martin (1939) (see also Bollenrath et al, 1941). For the special cases of the Voigt grain-interaction model (Voigt, 1910) and the Reuss grain-interaction model (Reuss, 1929), it was demonstrated that such XECs can be applied (Mö ller & Martin, 1939).…”
Section: Macroscopically Elastically Isotropic and Anisotropicmentioning
confidence: 99%
“…diffraction strains differ from mechanical strains due to the intrinsic elastic anisotropy. Diffraction (X-ray) elastic constants were eventually proposed on an empirical basis by Mö ller & Martin (1939) (see also Bollenrath et al, 1941). For the special cases of the Voigt grain-interaction model (Voigt, 1910) and the Reuss grain-interaction model (Reuss, 1929), it was demonstrated that such XECs can be applied (Mö ller & Martin, 1939).…”
Section: Macroscopically Elastically Isotropic and Anisotropicmentioning
confidence: 99%
“…the direction-dependent deformation behavior of the crystallites the material is composed of, was recognized and taken into account (see e.g. Glocker, 1938;Mö ller & Martin, 1938;Bollenrath et al, 1941). Based on different assumptions regarding the grain interaction, various models were developed to calculate the diffraction elastic constants (DEC) S 1 hkl and 1 2 S hkl 2 for stress analysis in materials with random crystallographic texture.…”
Section: Introductionmentioning
confidence: 99%